English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-24 07:49:40 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

Hi,

For this question, you're going to use the FOIL Method, just like what you would use for polynomials.

First ; Outer ; Inner ; Lasts

9 + 3sqr 7 - 3sqr 7 - sqr 7 squared

9 - 7 = 2

I hope that helps you out!

Please let me know if you have any other questions!

Sincerely,

Andrew

2007-05-24 08:14:11 · answer #1 · answered by The VC 06 7 · 0 0

3^2 - (√7)^2= 9 - 7 = 2

2007-05-24 15:03:55 · answer #2 · answered by Anonymous · 0 1

9 - 7 = 2

Remember from algebra?
(x+y)(x-y) = (x² - y²)

3² - √7² = 9 - 7 = 2
.

2007-05-24 14:53:46 · answer #3 · answered by Robert L 7 · 3 1

(3-squareroot 7)(3+square root7)
=(3)^2-(square root7)^2[(a-b)(a+b)=a^2-b^2]
=9-7=2 ans

2007-05-24 20:04:11 · answer #4 · answered by alpha 7 · 0 0

fedest.com, questions and answers